(untitled) (International Journal of Communication Systems and Network Technologies, 2018)
Hiding information can be accomplished using different techniques. This paper is a review of various images based hiding of secret data which can be a text or another image. The common framework is not tamper proof. Undoubtedly, the most trustworthy techniques is block-based, edge adaptive and uses a least significant bit approach. This falls in the spatial domain. Cryptography is storing and transmitting the information in such a way that it can only be obtained by authorized receiver.